The News Media and the Expectation Formation of Firms - Teresa Buchen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Forming expectations about the future path of the economy and the own business prospects is not costless for a fi rm. Instead, acquiring and processing the relevant macroeconomic information requires valuable resources. One important source of information that provides a coding service is the mass media. This paper investigates empirically whether the news media have an independent influence on the expectation formation process of fi rms that goes beyond the actual economic developments. Using the Ifo survey data that explicitly measure business expectations, and data that cover the intensity and the tone of media coverage, we come to three conclusions. First, a fi rm is more likely to update its business expectations when the volume of macroeconomic news rises. Second, the news media act as an amplifi er of actual economic developments. Third, business expectations react stronger to negative than to positive news.
Keywords: D84; E32; D89; 330